Osmotic Behavior of Bacterial Protoplasts: Temperature Effects - Eisenberg, A. D. (1973)
Among protoplasts released from cells of Bacillus megaterium grown at 20, 30, or 37 C, osmotic swelling in NaCl solution at a given external osmotic pressure was greatest for protoplasts from cells grown at 20 C and least for protoplasts from cells grown at 37 C. Protoplasts from cells grown at lower temperaturs were also less stable to osmotic shock and lysed at higher external osmotic pressures than did protoplasts from cells grown at higher temperatures. But for cells grown at any one temperature, osmotic stabilization was itself temperature dependent so that the higher the ambient incubation temperature, the higher the osmotic pressure needed to prevent lysis of a given fraction of the input protoplast population. However, comparison of the osmotic stability of protoplasts from cells grown at different temperatures at various ambient incubation temperatures revealed that, except at 5 C where no differences were discerned, protoplasts from cells grown at lower temperatures still lysed at higher osmotic pressures than did those from cells grown at higher temperatures. The apparent internal osmolality (28 to 31 atm) did not vary significantly among whole cells from the three growth temperatures. Therefore, the observed differences in osmotic behavior could not be attributed to changes in internal osmotic pressure. Rather, it seemed likely that the differences were due to changes in membrane properties.